Ecological knowledge of the species of Mangrove Button (Conocarpus Erectus): the tour in the National Park of Jericoacoara - Ceará (Research, Society and Development, 2021)
Tourism in the sustainable crescent acts in an experiment to reduce the main impacts related to the intrusive behavior of travelers and tour guides, an action capable of generating an imbalance in the environment and in the receiving populations, populations that are inserted in this context. The research, therefore, aimed to assess the ecological understanding of the guides (drivers) about the species (Conocarpus erectus) and verified whether the perception interferes in the manner of conservation of the species. Following the methodological procedures of this study, 30 questionnaires were applied at Praia do Preá, in the city of Cruz/CE, with guides (drivers) linked to Cooperturpreá. When applying the questionnaires, our main objective was to profile the guides (drivers) and assess the level of ecological knowledge about the Park's vegetation, more specifically about the Button Mangrove (Conocarpus erectus), the Sloth Tree. The approach used for data collection was quantitative and qualitative. This research made it possible to verify that the guides (drivers), for the most part, in fact have an understanding of the Mangue de Botón (Conocarpus erectus) species, although they do not have mastery of technical terms, they have ecological knowledge about the species, they demonstrate knowledge about the life cycle, flowering and fruiting of the species, however it is recommended to further investigate this ecological knowledge about the species under study.